A new species of soil mites (Acari: Mesostigmata: Zerconidae) from Afyonkarahisar province, Turkey. Issue 1 (2nd January 2017) - Duran, Elif Hilal; Karaca, Mehmet; Urhan, Raşit
Abstract : Zercon arslani sp. n. is described and illustrated from female and male specimens collected in Afyonkarahisar province, Turkey. A short description and important morphological features of Prozercon plumosus Călugăr, 2004, which is a new record for the Turkish acarofauna, are also given with drawing. Informations on habitat and distribution for each species are also provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:BD823E8D-E13A-4C6C-A84B-DE4979BF55F8